Bose-Einstein condensation in a rotating anisotropic TOP trap - Arlt, J; Marago, O; Hodby, E; Hopkins, SA; Hechenblaikner, G; Webster, S; Foot, C (IOP, 1999)
We describe the construction and operation of a time-orbiting potential trap that has different oscillation frequencies along its three principal axes. These axes can be rotated and we have observed Bose-Einstein condensates of 87Rb with a rotating ellipsoidal shape. Under these conditions it has been predicted that quantized vortices form and are stable.